Pietism and War - Krzysztof Gładkowski (Chrześcijaństwo-Świat-Polityka)
Text takes up the theme of Pietism, whose representatives developed — both intellectually and practically — the question of building a better world, in the context of numerous wars, and religious wars at that. This seemingly historical movement within the Lutheran Church and other Protestant denominations pointed to the message of the Gospel of Christ and continues to evolve. This makes it still relevant today, since the Christian message — as in Pietism — is primarily directed towards the inner transformation of man and the formation of community relationships. The context in which Pietism emerged was that of the above-mentioned wars, but also of migrations, which makes Pietism heuristically relevant even today, given the many wars and refugees in situations of political and religious tension. Due to the limited length of this text, the author deals only with selected issues. These include: the definition and classification of pietism, the ideas of classical pietism, and an example of radical pietism. In both classical and radical pietism, the question of attitudes to war is highlighted.